2017
DOI: 10.1177/0284185117707359
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation force impulse imaging for detection of liver fibrosis in overweight and obese children

Abstract: Background Acoustic radiation force impulse (ARFI) is a non-invasive alternative to a liver biopsy for the evaluation of liver fibrosis (LF). Purpose To investigate the potential usefulness of acoustic radiation force impulse ARFI for detecting LF in overweight and obese children Material and Methods A cross-sectional study was conducted in 148 schoolchildren. A diagnosis of non-alcoholic fatty liver disease (NAFLD) and LF was based on ultrasound (US) and ARFI shear wave velocity (SWV). Results The laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…24,50 Only one study has been published utilizing ARFI in children with NAFLD but, in this European cohort, the NAFLD diagnosis was not made via biopsy. 51 Another form of elastography, magnetic resonance elastography (MRE), was not analyzed in this study. While MRE has somewhat comparable accuracy to ultrasound-based elastography, it has some significant drawbacks such as cost and increased test time.…”
Section: Discussionmentioning
confidence: 99%
“…24,50 Only one study has been published utilizing ARFI in children with NAFLD but, in this European cohort, the NAFLD diagnosis was not made via biopsy. 51 Another form of elastography, magnetic resonance elastography (MRE), was not analyzed in this study. While MRE has somewhat comparable accuracy to ultrasound-based elastography, it has some significant drawbacks such as cost and increased test time.…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic radiation force impulse (ARFI) is a non-invasive technique integrated into an US machine that uses sound waves to induce shear waves that propagate along the US beam. The method has been validated in adult NAFLD patients and results are promising in pediatric patients as well [ 66 ]. Although sample size was generally small in pediatric studies [ 67 , 68 ] and some authors included patients with diverse liver disease etiologies [ 69 , 70 ] the results indicated that ARFI could represent an adequate predictor of hepatic fibrosis [ 71 ].…”
Section: ⧉ Imagistic Evaluationmentioning
confidence: 99%
“…The results showed that children with laboratory parameters in the range of normal values, but also some with normal liver ultrasounds or with mild fatty infiltration, may in fact have had a significant degree of liver fibrosis. [ 48 ] ARFI is not only useful for the evaluation of pNAFLD in normal-weighed children, but also in obese patients or in children with ascites [ 49 ]. ARFI has shown an excellent correlation with the AST/ALT ratio in obese children and can be used as a non-invasive tool to detect pNAFLD and related hepatic parenchymal changes, especially in pediatric patients where biopsy is not a desired method [ 50 ].…”
Section: Elastographymentioning
confidence: 99%